Granulocyte and Monocyte Adsorption Apheresis for Generalized Pustular Psoriasis: Therapeutic Outcomes in Three Refractory Patients. Issue 4 (August 2015) - Fujisawa, Tomomi; Suzuki, Satoko; Mizutani, Yoko; Doi, Tomoaki; Yoshida, Shozo; Ogura, Shinji; Seishima, Mariko
Abstract Generalized pustular psoriasis (GPP) is a type of neutrophilic dermatosis that is sometimes resistant to medications. In patients with neutrophilic skin diseases, granulocyte and monocyte adsorption apheresis (GMA) has been demonstrated to selectively and efficiently eliminate myeloid‐lineage leukocytes from the peripheral blood. We evaluated the efficacy and safety of repeated GMA therapy in three refractory GPP patients. Three GPP patients refractory to previous therapies received weekly GMA with five sessions per course, which was repeated when the symptoms reappeared. The efficacy was assessed by the disease severity scores 2 weeks after each course of GMA. The GPP severity scores of all three patients were reduced in all courses (N = 9); they were reduced by more than 3 points in six courses and by 2 points in three courses. After the first GMA course, the GPP severity scores were reduced by more than 3 points in all three patients. On average, the GPP severity scores were reduced by 4.67 and 3.67 points after the first course and repeated courses, respectively. The severity of edema and pustules were particularly improved in all patients and no adverse effects were observed. GMA showed efficacy for the treatment of refractory GPP patients as a non‐pharmacologic intervention without any associated adverse effects, and was particularly effective in the first course, but also effective in the subsequent courses.